The EPAS1 gene influences the aerobic-anaerobic contribution in elite endurance athletes - Henderson, J.; Withford-Cave, J. M.; Duffy, D. L.; Cole, S. L.; Sawyer, N. A.; Gulbin, J. S.; Hahn, A.; Trent, R. J.; Yu, B. (Human Genetics, 2005)
EPAS1 is a gene involved in complex oxygen sensing. It is expressed in microvascular endothelial cells, lung epithelial cells, cardiac myocytes and the brain. An association study was undertaken comparing elite endurance athletes classified into two groups according to a power-time model of performance intensity: power-time-maximum (PT-MAX; N=242, event duration 50 s to 10 min) and power-time-steady state (PT-SS; N=151, event duration ~2-10 h), with normal controls (N=444) using 12 SNPs across EPAS1. Ordinal regression analysis of allele frequencies revealed significant differences at SNPs 2 and 3 (P=0.01). Haplotype analysis revealed the presence of haplotypes involving SNPs 2-5 that significantly differentiated (P<0.05) the groups based on an ordinal ranking using the power-time classification. These same haplotypes differentiated the PT-MAX group in which a significant decrease in a haplotype (F: G-C-C-G; OR=0.57, P=0.02, 95% CI 0.36-0.92) and increase in a second haplotype (G: A-T-G-G; OR=1.75, P=0.03, 95% CI 1.05-2.91) was observed compared to controls. The PT-SS group was differentiated from the PT-MAX group by a third haplotype (H: A-T-G-A; OR=0.46, P=0.04, 95% CI 0.22-0.96). Since EPAS1 has a role as a sensor capable of integrating cardiovascular function, energetic demand, muscle activity and oxygen availability into physiological adaptation, we propose that DNA variants in EPAS1 influence the relative contribution of aerobic and anaerobic metabolism and hence the maximum sustainable metabolic power for a given event duration.